Soybean Hairy Root Transformation: A Rapid and Highly Efficient Method. Issue 7 (19th July 2021) - Song, Jaehyo; Tóth, Katalin; Montes‐Luz, Bruna; Stacey, Gary
Abstract: New genetic engineering techniques have advanced the field of plant molecular biology, and Agrobacterium ‐mediated transformation has enabled the discovery of numerous molecular and genetic functions. It has been widely used in many plants, including the economically important crop, soybean. Large‐scale genetic analyses are needed to comprehend the molecular mechanisms that underlie the agronomic traits of soybean, and the generation of stable transgenic plants involves a lengthy and laborious process. Agrobacterium rhizogenes ‐mediated hairy root transformation is a quick and efficient method for investigations of root‐specific processes and interactions. Generation of composite plants with transgenic roots and wild‐type shoots allows for the study of the genetic mechanisms involved in root biology, such as the Bradyrhizobium ‐soybean interaction. Here, we provide an updated protocol for generating hairy soybean roots in as little as 18 days in a cost‐ and space‐effective manner and demonstrate possible uses of composite plants with soybean nodulation assays and gene expression analysis as examples. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Soybean hairy root transformation Basic Protocol 2 : Soybean nodulation assay Alternate Protocol : Soybean nodulation assay in germination pouches Support Protocol : Bradyrhizobium japonicum culture preparation for inoculation Basic Protocol 3 : Histochemical GUS staining for promoter analysis